Produção e caracterização de arcabouços tridimensionais baseados em quitosana, polidopamina e hidroxiapatita para aplicações na engenharia tecidual óssea - Andrade, Gabriela Santos (2024)
Three-dimensional scaffolds should serve as a temporary environment for cell growth, with biodegradability at controlled rates, as well as mechanical properties like the area where they are applied. Chitosan (CHI) has promising properties, and its characteristics can be improved with the addition of hydroxyapatite (HA) and polydopamine (PDA). HA is a bioactive ceramic whose composition corresponds to the mineral phase of bones. To the best of our knowledge, PDA has not yet been investigated in addition to CHI and HA to produce scaffolds. PDA coating can be promising, due to its biocompatibility, cell adhesion and relatively slow degradation. Therefore, this study aimed to prepare and characterize 3D chitosan (CHI) and hydroxyapatite (HA) scaffolds coated with polydopamine (PDA) and test aspects of their applicability in bone tissue engineering. The present research also studies different concentrations of dopamine polymerization and contact time for scaffolds coating. First, CHI scaffolds were prepared with different coatings (1, 2, 3 and 4 mg/mL) within periods of 0.5h, 1h, 3h, 6h, 12h and 24h. They were compared with the uncoated CHI scaffold FTIR, SEM and compression test. After the coating standardization, groups including HA were tested. The groups were produced with different formulations of the three materials, comparing the presence or absence of PDA coating. In addition to the above characterizations, EDS, porosity analysis, XRD, TGA, DSC, in vitro degradation and cell viability assay were performed. It was found the interaction between CHI and PDA and more uniform layer for the groups with the highest coating concentration. These also showed greater potential for resistance to compressive loads. The interaction of the polymers and HA was also suggested. They exhibited suitable resistance to compressive loads at areas that do not require high stress load. Its microstructure showed heterogeneous porosity patterns and its surface became rougher with the inclusion of HA and PDA. Also, CHI/HA/PDA (50/50) displayed interconnected pores with long channels microstructure. MTT cytotoxicity assay demonstrated the groups cell viability, the scaffolds similar behavior to negative control group (p > 0.05) reveals their biocompatible potential. This information appears to be favorable for the materials employment, under these conditions, for bone tissue engineering.